A Comparative Study on the Structure and Properties of α‐amylase‐ and Pullulanase‐Modified Starch‐Polyvinyl Alcohol‐Based Nanocomposite Films. (1st March 2019) - Gao, Chengcheng; Lu, Yue; Yu, Chen; Tang, Xiaozhi
Abstract : Starch‐based nanocomposites have been popular in food packaging for decades, particularly starch‐polyvinyl alcohol‐nanoparticle systems. To further improve the performance of these nanocomposites, α‐amylase, and pullulanase are used to adjust the structure and properties of the starch‐polyvinyl alcohol (PVOH)‐laponite RD (LRD) nanocomposite films. The α‐amylase‐treated films show increased elongation at break (E%) and decreased tensile strength (TS). The increased E% primarily results from the uniform dispersion of LRD and the improved miscibility between each component. Low molecular weight polysaccharides obtained by the hydrolyzation of starch function as plasticizers. The decreased molecular weight of starch leads to less physical entanglements of polymer chains and a decreased TS. The pullulanase‐treated films show an increased TS and decreased E%. These results are attributed to the increased amylose content. Amylose tends to reorganize and form intramolecular hydrogen bonds, thus resulting in an increased TS. The decreased miscibility between each component mainly contributes to the decreased E%. This study shows that α‐amylase and pullulanase alters the structure and properties of starch‐based nanocomposites in different manners and shows great potential in controlling the performance of starch‐based nanocomposites. Abstract : Pullulanase and α‐amylase are used to adjust the propertie s of starch‐polyvinyl alcohol(PVOH)‐nanoparticle laponite RD (LRD) nanocomposites. α‐Amylase improved the distribution of LRD in the matrix and the miscibility between starch, PVOH and LRD. Pullulanase displayed the opposite trend. α‐Amylase‐treated films displayed increased elongation at break (E%) and decreased tensile strength (TS). Pullulanase‐treated films demonstrated decreased E % and increased TS.